Regularity of contact with GPs: Measurement approaches to improve valid associations with hospitalization - Youens, David; Harris, Mark; Robinson, Suzanne; Preen, David B; Moorin, Rachael E (2019)
Background: Studies examine longitudinal continuity of GP contact though few consider 'regularity of GP contact', i.e., the dispersion of contacts over time. Increased regularity may indicate planned ongoing care. Current measures of regularity may be correlated with the number of contacts and may not isolate the phenomenon of interest. Objectives: To compare two published and one newly developed regularity index in terms of their ability to measure regularity of GP contacts independently of the number of contacts and the impact on their association with hospitalization. Methods: A cohort at risk of diabetes-related hospitalization in Western Australia from 1990 to 2004 was identified using linked administrative data. For each regularity index, relationships with number of GP contacts were assessed. Hospitalization was then regressed on each index with and without number of contacts as a covariate. Results: Among 153,414 patients the new regularity index showed a reduced association with number of contacts compared with existing indices. Associations with hospitalization differed between measures; for previously published indices, there were no significant associations between regularity and hospitalization, whereas on the new index, most regular GP contact was associated with reduced hospitalization (IRR = 0.90, 95% CI = 0.88-0.93). When number of contacts was added as a covariate, point estimates for this index showed little change, whereas for existing measures this addition changed point estimates. Conclusion: A new measure of regularity of GP contact was less correlated with the number of contacts than previously published measures and better suited to estimating unconfounded relationships of regularity with hospitalization.